Government Policy In Coastal Management And Small Island Muna Regency, Indonesia - La Ode Restele; La Ode Sahaba; La Ode Muh Munadi (Publisher Cv. Inara, 2021)
Improving the management of coastal areas and small islands needs to have the support of the State of Indonesia as the world's maritime axis area because it has abundant fisheries and marine wealth. The study was conducted in Muna Regency in April-June 2021 with the determination of the location of purposive sampling in the archipelago. Research uses qualitative and quantitative approaches with data collection methods including observations, interviews and document studies using SWOT analysis. The results of the study showed the Muna Regency government in improving the management of coastal areas and small islands provides convenience and support both namely financial access, coaching, counseling and assistance for fishing communities.